Influencia de la práctica pedagógica docente en el desinterés por el aprendizaje del inglés en estudiantes de la I.E. N' 60304 Jorge Basadre Grohman Mazán Loreto 2024 - Huaninchi Sanchez, Mercedes Viviana (2025)
The primary objective of this study was to elucidate the influence of pedagogical teaching practice on disinterest in English language learning among students at I.E. N° 60304 Jorge Basadre Grohman, Mazán, Loreto, during the year 2024. Methodologically, the research was framed within an explanatory approach, employing a field-based, bivariate, and cross-sectional design. The study considered a population of 483 students, of which a sample of 120 were selected. Data collection was conducted using a survey technique through structured questionnaires, which were validated by experts in the field. The findings revealed a significant influence of pedagogical teaching practice on disinterest in English language learning. A simple regression analysis indicated that effective teaching contributes to mitigating such disinterest, as evidenced by the negative coefficient (β = -0.479) and the p-value (p = .000), leading to the rejection of the null hypothesis. Furthermore, the coefficient of determination (R² = .229) suggested that pedagogical teaching practice accounts for 22.9% of the variability in disinterest toward English language learning. In conclusion, enhancing pedagogical strategies emerges as a critical factor in fostering a more positive attitude toward language acquisition.